2017
DOI: 10.1177/1756827717706009
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of flame instabilities in narrow channels: Laminar premixed methane/air combustion

Abstract: Premixed flames propagating within small channels show complex combustion phenomena that differ from flame propagation at conventional scales. Available experimental and numerical studies have documented stationary, non-stationary, or asymmetric modes that depend on properties of the incoming reactant flow as well as channel geometry and wall temperatures. This work seeks to illuminate mechanisms leading to symmetry breaking and limit cycle behavior that are fundamental to these combustion modes. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The FREI phenomenon has been investigated for a methane/air mixture in a series of works [18,[25][26][27]. Miyata et al [26] studied the unsteady behavior of the oscillating flames and the FREI for methane/air premixed combustion in microchannels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FREI phenomenon has been investigated for a methane/air mixture in a series of works [18,[25][26][27]. Miyata et al [26] studied the unsteady behavior of the oscillating flames and the FREI for methane/air premixed combustion in microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…Varying these parameters, the flame can become stable or experience repeated extinctions and ignitions [11,21,29,30]. It is important to highlight that the models and the methods employed in this work have been accepted and acknowledged in the literature [24,27]. In the following sections, the simulation methodology is described.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant chemical and diffusive processes underlying the hot- and cool-flame dynamics will be revealed, which would be of fundamental and practical importance for the design of advanced combustion systems. Furthermore, some recent studies observed the repetitive ignition and extinction (FRIE) event in microchannel flow reactors with an imposed temperature stratification. The coupling of inlet flow with the propagating flame front that depends on the local temperature gradient was responsible for the FRIE dynamics. However, when considering the effectiveness of the mixture equivalence ratio or stoichiometry stratification, as well as the intertransition between hot- and cool-flame fronts, the FRIE dynamics would become much more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations for both premixed and non-premixed (diffusion) combustion at micro scales have been evolving extensively as the topic is becoming more and more interesting to researchers. In premixed combustion, researchers have concluded that combustion characteristics and flame behavior are very sensitive to the dimensional and thermo-physical parameters [3][4][5][6]. Other than premixed combustion at micro scales, non-premixed or diffusion combustion at such scales has also been under great attention due to the fact that diffusion combustion is a more typical combustion regime to use in practical systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical study of micro-jet hydrogen/methane diffusion flames by Gao et al[27]. Top: Computed temperature contours and heat release rate (HRR) isopleths for CH4 flames at fuel jet velocity of 0.4 m/s for (a) T b = 1800 K (b) T b = 300 K, and for H 2 flames at 1.0 m/s for (c) Tb = 1800 K (d) T b = 300 K; Bottom: Computed temperature contours and HRR isopleths at the thermal conductive burner condition (the thermal conductivity of burner wall is 16 W/m-K) for (a) H 2 flame at 2.0 m/s, (b) H 2 /CH 4 80%/20% flame at 1.2 m/s, (c) H 2 /CH 4 20%/80% flame at 0.6 m/s, (d) CH 4 flame at 0.5 m/s. Here the flame temperatures range between 2028 K and 2034 K.…”
mentioning
confidence: 99%